Traumatic brain injury, temperament, and violence in incarcerated youth: a mediation analysis based on Delisi and Vaughn’s theory of temperament and antisocial behavior - Veeh, Christopher A. (Psychology, crime & law, 2018)
Traumatic brain injury (TBI) is associated with violent behavior. A possible key mechanism to explain the relationship between TBI and violence is DeLisi and Vaughn’s temperament-based theory of antisocial behavior. Accordingly, the current study investigates whether temperament - the combination of effortful control and negative emotionality - mediates the relationship between TBI and violent behavior within incarcerated youth. A non-probability sample of youth (N = 227) incarcerated in two long-term residential facilities completed a comprehensive assessment tool that collected data on TBI, temperament, childhood trauma, substance use, mental illness, and a variety of demographic characteristics. Preliminary results showed TBI significantly increased violent behavior, adjusting for confounds. Then, mediation analysis found that temperament accounted for 54% of the total effect between TBI and violence. The study findings show the potency of DeLisi and Vaughn’s temperamental construct in explaining the relationship between TBI and violent behavior within a sample of incarcerated youth. The dynamic interplay between effortful control and negative emotionality appears to be an important mechanism related to violent behavior. Both temperament constructs should be the focus of future assessment and intervention among incarcerated youth with TBI.